(untitled) (Annals of Medical Research, 2021)
Aim: The aim of this study was to investigate the microhardness of sonic-activated and high-viscosity bulk-fill resin-based composites (RBCs) in different shades polymerized by using two different light emitting diode (LED) light curing units (LCUs).Material and Methods: Eight groups (n=4) of composite samples with two different shades (A2, A3) of sonic-activated bulk-fill RBCs (SonicFill™) and high-viscosity bulk-fill RBCs (Reveal HD Bulk) were prepared to evaluate the Vickers microhardness (VMH) values. To collect microhardness data for both the upper and the lower sample surfaces, the cylindrical bulk-fill RBC samples with a depth of 4 mm and diameter of 10 mm were cured with two different LED LCUs (Valo Ultradent, Ultradent Products Inc., South Jordan, UT; Demi Ultra, Kerr Dental, USA) with the light-guide tip positioned in contact with a glass slide on the upper surface of the samples. Three-way ANOVA and Student’s t-test analyses were performed with the results obtained. Comparisons were performed using a significance level of p0.05.Results: The type of bulk-fill RBC and the interaction between the type of LED LCU and shade had significant effects on the microhardness of the composites (p=0.009; p0.01). Although the bottom surfaces of the two shades of SonicFill showed lower microhardness values than the top surfaces did (p0.05). Although A2 SonicFill showed significantly higher microhardness values than A2 Reveal HD did when polymerized with the two LED LCUs (p0.05).Conclusion: Differences in microhardness among the materials are suggested to be dependent on the types and shades of bulk-fill RBCs and LED LCUs.